Design thinking dalam perancangan user interface dan user experience website desa jurang - Maulana, Muhammad Hanif; darmanto, eko (Universitas Muhammadiyah Riau, 2024)
The rapid development of information technology has had a significant impact on various aspects of life, including life in rural areas. One of the challenges faced by many villages is the limited access to information, which can lead to misunderstandings between the village government and its citizens. The lack of transparency in information delivery hampers public participation in decision-making and village development. In this regard, a village website can be an effective solution to improve information access by providing important data such as announcements, activities, and public services. The design of the village website must consider ease of access and user comfort. Therefore, this research aims to design the User Interface (UI) and User Experience (UX) of the village website using the Design Thinking method. This method focuses on user needs by creating intuitive, user-friendly, and informative designs. The result of this research is a prototype of the village website, designed with attention to information readability and ease of navigation. This prototype can serve as a reference for the development of other village websites to enhance transparency, accountability, and public participation in village activities. Thus, it is expected that this village website will strengthen the relationship between the village government and the citizens, as well as accelerate the development process at the village level.